Patient-Derived Tumor Organoids Can Predict the Progression-Free Survival of Patients With Stage IV Colorectal Cancer After Surgery. Issue 5 (9th March 2023) - Wang, Ting; Tang, Yuting; Pan, Wenjun; Yan, Botao; Hao, Yifan; Zeng, Yunli; Chen, Zexin; Lan, Jianqiang; Zhao, Shuhan; Deng, Chuxia; Zheng, Hang; Yan, Jun
Abstract : BACKGROUND: Recent studies have shown patient-derived tumor organoids can predict the drug response of patients with cancer. However, the prognostic value of patient-derived tumor organoid–based drug tests in predicting the progression-free survival of patients with stage IV colorectal cancer after surgery remains unknown. OBJECTIVE: This study aimed to explore the prognostic value of patient-derived tumor organoid–based drug tests in patients with stage IV colorectal cancer after surgery. DESIGN: Retrospective cohort study. SETTINGS: Surgical samples were obtained from patients with stage IV colorectal cancer at the Nanfang Hospital. PATIENTS: A total of 108 patients who underwent surgery with successful patient-derived tumor organoid culture and drug testing were recruited between June 2018 and June 2019. INTERVENTIONS: Patient-derived tumor organoid culture and chemotherapeutic drug testing. MAIN OUTCOMES MEASURES: Progression-free survival. RESULTS: According to the patient-derived tumor organoid-based drug test, 38 patients were drug sensitive and 76 patients were drug resistant. The median progression-free survival was 16.0 months in the drug-sensitive group and 9.0 months in the drug resistant group ( p < 0.001). Multivariate analyses showed that drug resistance (HR, 3.38; 95% CI, 1.84–6.21; p < 0.001), right-sided colon (HR, 3.50; 95% CI, 1.71–7.15; p < 0.001), mucinous adenocarcinoma (HR, 2.47; 95% CI, 1.34–4.55; p = 0.004), and non-R0 resection (HR, 2.70; 95% CI, 1.61–4.54; p < 0.001) were independent predictors of progression-free survival. The new patient-derived tumor organoid–based drug test model, which includes the patient-derived tumor organoid–based drug test, primary tumor location, histological type, and R0 resection, was more accurate than the traditional clinicopathological model in predicting progression-free survival ( p = 0.001). LIMITATIONS: A single-center cohort study. CONCLUSIONS: Patient-derived tumor organoids can predict progression-free survival in patients with stage IV colorectal cancer after surgery. Patient-derived tumor organoid drug resistance is associated with shorter progression-free survival, and the addition of patient-derived tumor organoid drug tests to existing clinicopathological models improves the ability to predict progression-free survival.